2013
DOI: 10.17221/165/2013-pse
|View full text |Cite
|
Sign up to set email alerts
|

The response of nitrifier, N-fixer and denitrifier gene copy numbers to the nitrification inhibitor 3,4-dimethylpyrazole phosphate

Abstract: A laboratory incubation experiment was conducted to examine the effects of 3,4-dimethylpyrazole phosphate (DMPP) on the transformation of urea-N and associated microbial communities in a low-fertility brown soil. The soil was supplied with urea at 180 kg N/ha and DMPP at 0, 1.8 or 18 kg/ha, while soil that was not supplied with urea and DMPP was treated as the control. Soil mineral nitrogen (NH 4 + -N and NO 3 --N) was measured at regular intervals, and temporal variations in the population sizes of nitrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The experimental treatments included the following: (1) no fertilizer (CK); (2) Conventional granular urea (N), containing 46% nitrogen; (3) Urea fertilizer supplemented with 1% hydroquinone (HQ), containing 45.55% nitrogen; (4) Urea fertilizer supplemented with 0.5% N-butylthiophosphoric triamide (NBPT), containing 45.77% nitrogen; (5) Urea fertilizer supplemented with 3% dicyandiamide (DCD), containing 44.66% nitrogen; (6) Urea fertilizer supplemented with 1% 3,4-dimethylpyrazole phosphate (DMPP), containing 45.55% nitrogen; (7) Urea fertilizer supplemented with 1% HQ and 3% DCD (HQ+DCD), containing 44.23% nitrogen; (8) Urea fertilizer supplemented with 0.5% NBPT and 1% DMPP (NBPT+DMPP), containing 45.32% nitrogen; (9) Sulfur-coated urea fertilizer (SCU) (120-day release period) produced by Han Feng Company in Canada, containing 34.00% nitrogen; (10) Resin-coated urea fertilizer (PCU) (120-day release period) produced by Shandong Jin Zheng Da Group, containing 43.00% nitrogen. Each treatment was replicated three times, with a plot area of 20 m 2 .…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental treatments included the following: (1) no fertilizer (CK); (2) Conventional granular urea (N), containing 46% nitrogen; (3) Urea fertilizer supplemented with 1% hydroquinone (HQ), containing 45.55% nitrogen; (4) Urea fertilizer supplemented with 0.5% N-butylthiophosphoric triamide (NBPT), containing 45.77% nitrogen; (5) Urea fertilizer supplemented with 3% dicyandiamide (DCD), containing 44.66% nitrogen; (6) Urea fertilizer supplemented with 1% 3,4-dimethylpyrazole phosphate (DMPP), containing 45.55% nitrogen; (7) Urea fertilizer supplemented with 1% HQ and 3% DCD (HQ+DCD), containing 44.23% nitrogen; (8) Urea fertilizer supplemented with 0.5% NBPT and 1% DMPP (NBPT+DMPP), containing 45.32% nitrogen; (9) Sulfur-coated urea fertilizer (SCU) (120-day release period) produced by Han Feng Company in Canada, containing 34.00% nitrogen; (10) Resin-coated urea fertilizer (PCU) (120-day release period) produced by Shandong Jin Zheng Da Group, containing 43.00% nitrogen. Each treatment was replicated three times, with a plot area of 20 m 2 .…”
Section: Experimental Designmentioning
confidence: 99%
“…As a result, soil nitrate reductase and denitrification enzyme activities decrease, leading to a reduction in nitrate leaching and N 2 O emissions [9]. Furthermore, research has shown that the use of nitrification inhibitors like 3,4-dimethylpyridyl phosphate (DMPP) markedly decreases the abundance [10] and transcript activity of ammonia-oxidizing archaea (AOA) and ammonia-oxidizing bacteria (AOB), which in turn alters the composition of AOB communities with respect to NH 4 + -N, NO 3 − -N, N 2 O, and pH [11][12][13]. By temporarily inhibiting urease-mediated urea decomposition, urease inhibitors extend the soil's retention time for ammonium ions, resulting in reduced ammonia volatilization and increased availability of NH 4 + for plant absorption [14].…”
Section: Introductionmentioning
confidence: 99%
“…Stabilized fertilizer showed a noticeably higher protease activity, which means that the inhibitor promoted the PG metabolisms and the microorganisms still had higher activity, and N turnover capacity, mainly due to the availability of nitrogen substrates by microorganism's absorption and utilization still be high compared with urea alone. Research showed that the nitrification inhibitor NBPT impeded the growth of ammoniaoxidizing archaea (AOA), and DMPP significantly reduced the ammonia oxidizing bacterial abundance, which significantly inhibited urea hydrolysis indirectly affecting nitrification (Dong et al 2013;Meng et al 2020). Geisseler et al (2010) showed that the N turnover was determined by the amount and species of N source.…”
Section: Activity Of Enzymes Related To Nitrogen Conversionmentioning
confidence: 99%